2015
DOI: 10.1186/s13031-015-0066-1
|View full text |Cite|
|
Sign up to set email alerts
|

Neonatal outcomes of Syrian refugees delivered in a tertiary hospital in Ankara, Turkey

Abstract: We retrospectively reviewed the medical records of all Syrian immigrants from the TurkishSyrian border who delivered the Zekai Tahir Burak Maternity and Teaching Hospital Neonatal Intensive Care Unit (NICU) in Ankara, Turkey. Between January 2013 and December 2014 a total of 36,346 women gave birth at this center. Of these, 457 women were Syrian immigrants, comprising 1.2 % (457/36,346) of all deliveries. The number of births among Syrian refugees in Turkey appears to be increasing. Further research is needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
28
4
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 7 publications
3
28
4
2
Order By: Relevance
“…These findings are congruent with findings from a Lebanese and a Turkish study that revealed an overall CS rate among Syrian refugee mothers of 35% and 36%, respectively (Büyüktiryaki et al. ; Huster ). In our study, previous CS was the most common cause of another CS and this might be because of the high reported rate of CS in Syria 20.6% (WHO ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are congruent with findings from a Lebanese and a Turkish study that revealed an overall CS rate among Syrian refugee mothers of 35% and 36%, respectively (Büyüktiryaki et al. ; Huster ). In our study, previous CS was the most common cause of another CS and this might be because of the high reported rate of CS in Syria 20.6% (WHO ).…”
Section: Discussionsupporting
confidence: 90%
“…) and Turkish study (Büyüktiryaki et al. ), which found that 11% and 9% of Syrian refugee mothers had LBW babies. Internationally, it is well documented that refugee women are more susceptible to having LBW babies (Kandasamy et al.…”
Section: Discussionmentioning
confidence: 94%
“…Approximately 40.0% gave birth at home at least once. The high fertility rate of the Syrian refugee women reveals the importance of the risk of transmission of the disease to the mother and the baby [46]. Among Syrian refugees, males, married, low educated and those over 50 years of age were exposed to hepatitis B virus more.…”
Section: Discussionmentioning
confidence: 99%
“…While many of these factors are related to being a refugee more broadly, the need for information in women’s own language is important, as it has been shown that the establishment of special care guides in their own language facilitates access to health services (Correa‐Velez & Ryan, ; Demirci et al, ). At the same time, it is necessary to have a sufficient number of interpreters in hospitals so that women do not feel alone during birth (Büyüktiryaki, Canpolat, Dizdar, Okur, & Şimşek, ). Nurses should advocate for these services to ensure that Syrian women are supported during pregnancy and the postpartum period.…”
Section: Discussionmentioning
confidence: 99%